Creative performance of millennials and generation Z: What matters more, intrinsic or extrinsic rewards? - Shwetha M. Krishna; Somya Agrawal (Administrative Sciences, 2025)
Millennials and Gen Z now dominate the global workforce, each with distinct reward preferences influencing motivation and creativity. Understanding these distinctions is critical for improving employee retention and performance. This research aims to evaluate the efficacy of intrinsic and extrinsic rewards for both cohorts. The main goals are to determine reward preferences, examine the mediation effects of moral importance of work and learning attitudes, and assess their impact on creative performance. Using online survey, data were collected from 319 individuals in India and analysed using confirmatory factor analysis and structural equation modelling. Results show that while intrinsic rewards were not significantly related to the moral importance of work for either generation, extrinsic rewards were linked to moral importance only for Gen Z. Extrinsic rewards also had no significant impact on learning attitudes for Gen Z, but they did for millennials. Additionally, the moral importance of work was unrelated to creative performance for millennials, but it had a significant impact on Generation Z. By examining these dynamics, this study aims to provide insights into generational shifts in workplace values in the Indian context, highlighting implications for employee's creative performance that align with each generation's unique priorities and ethical considerations.
Keywords: 350; millennials; Gen Z; intrinsic rewards; extrinsic rewards; moral importance ofwork; learning attitude; creative performance